A Single Notch Semi-Circle UWB Antenna with Partial Ground Plane - Z. Mahmud, M.; Samsuzzaman, M.; Misran, N.; Ansarudin, F.; T. Islam, M.; A. Nasser, A.; Amin, N. (International Journal of Engineering and Technology, 2019)
This work presents an ultra-wideband (UWB) antenna with single notch band characteristics. The proposed antenna is composed on a simple, low loss and compact planar commercially available Rogers RT/Duroid 5870 substrate. The antenna is designed with a modified semi-circular radiating patch on one side and modified partial ground plane on the other side of double layer substrate. The semicircular patch is modified by etching a circular slot which assist to achieve the stop band at 4 GHz C band frequency range. The ground structure and the substrate materials are optimized to achieve desired performance of proposed antenna prototype. The proposed antenna prototype is designed, fabricated and measured. The measured results display that the prototyped antenna has achieved impedance bandwidths of 13.5 GHz (1.5 to 15 GHz) with a single frequency band-stop performance of 3.58 â€“ 4.92 GHz. The optimized antenna offers higher gain, almost stable radiation patterns and adequate radiation efï¬ciency over the operating bandwidth.Â Â